Perlindungan Hukum terhadap Pemegang Hak Cipta pada Film Layar Lebar (Jakarta Vs Everybody) yang Ditayangkan Secara Ilegal pada Aplikasi Telegram - Rizki Wahidah Lubis; Rizal Rizal (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This is to legally protect copyright holders against violations of illegal access via the Telegram application as well as knowing the implementation of law enforcement on copyright against illegal downloads on the internet. Films or cinematographic works that are protected by Law No.28 of 2014 concering copyright. However, in reality, many other parties copy copyrighted works without permission from the copyright holder. One example of a film that has experienced illegal duplication is the film Jakarta vs Everybody, starring Jefri Nichole. This multiplication occurs not only on the internet/VCD, but also on a social media application, namely Telegram. This research uses a normative juridical method with an approach to applicable laws and regulations, a case problem approach, as well as a literature study wihch is analyzed qualitatively. The result of the research show that currently there are still illegal films circulating in society and there is no awareness that accessing films illegal is a from of violation. The government needs to take firmer action in monitoring and blocking unofficial online sites. The government also needs to disseminate information to the public regarding the rights owned by the creator or copyright holder of a work and provide information regarding the legal consequences and copyright violations.